Durasi Penggunaan Media Sosial dengan Kualitas Tidur dan Kestabilan Emosi pada Mahasiswa Keperawatan Tahun 2023 - Imelda Hardiyanti Utami; Nurul Ainul Shifa; Nining Rukiah (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of technology and information has had an impact on students, especially those who actively use social media. The busyness and activities of students who are active in using social media, especially at night, can lead to poor sleep quality. Exposure to unhealthy content such as cyberbullying, body shaming, and social comparison can affect a person's emotional stability. To determine the relationship between the duration of social media use, sleep quality, and emotional stability. The sampling technique in this research uses Quota Sampling, and 122 nursing students out of a total of 175 were obtained. This research uses a quantitative method with a correlational study type, adopting a Cross-Sectional study approach. Statistical tests using the Chi-Square test with a sensitivity level of α = 0.05% or 95%. The results of the relationship between the duration of social media use and sleep quality show a value of p = 0.003 < α = 0.05. Meanwhile, the results of the relationship between the duration of social media use and emotional stability show a value of p = 0.001 < α = 0.05. There is a relationship between the duration of social media use, sleep quality, and emotional stability. The higher the use of social media, the worse the sleep quality and the lower the emotional stability.